Mackerel Fish Soup Supplementation on Hemoglobin Levels Among Second-Trimester Pregnant Women with Anemia - Eti Eliza; Reny Retnaningsih; Raden Maria Veronika Widiatrilupi (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Several maternal and neonatal health issues can contribute to anemia in pregnant women, which is a significant public health concern, particularly during the second trimester. Iron supplementation should be accompanied by local dietary adjustments focused on dietary intake. As an essential component in hemoglobin production, mackerel (Rastrelliger kanagurta) is a good source of animal protein due to its high iron and vitamin B12 content. This study aimed to assess changes in hemoglobin levels following mackerel soup supplementation among second-trimester pregnant women with mild anemia. The study used a pre-experimental one-group pretest-posttest design with a total sampling technique involving 32 participants. The intervention consisted of 200 ml of mackerel soup containing 100 grams of mackerel, administered twice a week for three weeks. Hemoglobin levels were measured before and after the intervention using a digital hemoglobin meter, and data were analyzed using a paired-sample t-test. A significant difference (p < 0.001) was observed, indicating that the mean hemoglobin level increased from 9.941 g/dL before the intervention to 11.053 g/dL after the intervention. In conclusion, mackerel soup supplementation may serve as a complementary food-based nutritional intervention to support the improvement of hemoglobin levels among second-trimester pregnant women with mild anemia.